Fixed and Variable Cost Principles for Financial Planning - Vandeveer, Monte L.; Langemeier, Michael R. (My University, 1994)
The purpose of this guide is to explain how fixed and variable costs should be used in the production decision-making process, both in the short and long run.
MF1006_1994-10
Keywords: MF1006; Economics; MF